Trends in Learning Religion through Digital Media: A Study of Students’ Perceptions of Religious Moderation - Rifqi Khoirul Ikhsan; Dewi Anggraeni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2026)
The development of digital media has given rise to a new trend in religious education: technoreligion, or technology-based religious practice. This study aims to map students’ perceptions of religious moderation through online religious education via websites and religious content they access. This is a qualitative study employing a netnographic approach, focusing on the observation of subjects within the online environment. Data collection techniques included questionnaires, online observation, interviews, and documentation. Meanwhile, the analysis utilized coding, pattern identification, and interpretation of research findings. The results indicate that students at UIN K.H. Abdurrahman Wahid are able to identify online websites that promote moderate religious understanding. The online websites used as references for religious learning include NU Online, Suaramuhamadiyah.id, Bincangsyariah.com, and Islami.co. Meanwhile, the content most frequently accessed in the study of religion relates to the History of Islamic Culture. Students’ perceptions regarding religious moderation are closely tied to the religious content they frequently access on digital media.